Preparation of Sandwich-like NiCo2O4/rGO/NiO Heterostructure on Nickel Foam for High-Performance Supercapacitor Electrodes - Li, Delong; Gong, Youning; Wang, Miaosheng; Pan, Chunxu (Nano-Micro Letters, 2016)
A kind of sandwich-like NiCo2O4/rGO/NiO heterostructure composite has been successfully anchored on nickel foam substrate via a three-step hydrothermal method with successive annealing treatment. The smart combination of NiCo2O4, reduced graphene oxide (rGO), and NiO nanostructure in the sandwich-like nano architecture shows a promising synergistic effect for supercapacitors with greatly enhanced electrochemical performance. For serving as supercapacitor electrode, the NiCo2O4/rGO/NiO heterostructure materials exhibit remarkable specific capacitance of 2644 mF cm−2 at current density of 1 mA cm−2, and excellent capacitance retentions of 97.5% after 3000 cycles. It is expected that the present heterostructure will be a promising electrode material for high-performance supercapacitors. Highlights: 1 A new sandwich-like NiCo2O4/rGO/NiO heterostructure is prepared by using a facile process via a three-step hydrothermal method. 2 This sandwich-like heterostructure exhibits a specific capacitance up to 2644 mF cm−2 and shows enhanced electrochemical performance.